2021
DOI: 10.7150/ntno.52361
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific membrane antigen (PSMA)-targeted photodynamic therapy enhances the delivery of PSMA-targeted magnetic nanoparticles to PSMA-expressing prostate tumors

Abstract: Enhanced vascular permeability in tumors plays an essential role in nanoparticle delivery. Prostate-specific membrane antigen (PSMA) is overexpressed on the epithelium of aggressive prostate cancers (PCs). Here, we evaluated the feasibility of increasing the delivery of PSMA-targeted magnetic nanoparticles (MNPs) to tumors by enhancing vascular permeability in PSMA(+) PC tumors with PSMA-targeted photodynamic therapy (PDT). Method: PSMA(+) PC3 PIP tumor-bearing mice were given a low-mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 57 publications
(61 reference statements)
0
17
0
Order By: Relevance
“…However, PC-3 PIP cells were inoculated to mice in medium in the study by Tschan et al [ 25 ], whereas PC-3 PIP cells were inoculated in medium:Matrigel matrix (1:1) in the present study (like for C4-2 cells; [ 16 ]), resulting in a very rapid PC-3 PIP tumor growth ( Figure S12 ). This may influence tumor stroma and vascular density, and, thus, radioligand uptake because vascular density tends to decrease with tumor growth [ 41 , 42 ]. Ngen et al found that higher vascular density enhanced delivery of their PSMA-targeted nanoparticles in the PC-3 PIP tumor peripheries compared to reduced delivery in the low vascularized areas in the centers of the tumor [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, PC-3 PIP cells were inoculated to mice in medium in the study by Tschan et al [ 25 ], whereas PC-3 PIP cells were inoculated in medium:Matrigel matrix (1:1) in the present study (like for C4-2 cells; [ 16 ]), resulting in a very rapid PC-3 PIP tumor growth ( Figure S12 ). This may influence tumor stroma and vascular density, and, thus, radioligand uptake because vascular density tends to decrease with tumor growth [ 41 , 42 ]. Ngen et al found that higher vascular density enhanced delivery of their PSMA-targeted nanoparticles in the PC-3 PIP tumor peripheries compared to reduced delivery in the low vascularized areas in the centers of the tumor [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may influence tumor stroma and vascular density, and, thus, radioligand uptake because vascular density tends to decrease with tumor growth [ 41 , 42 ]. Ngen et al found that higher vascular density enhanced delivery of their PSMA-targeted nanoparticles in the PC-3 PIP tumor peripheries compared to reduced delivery in the low vascularized areas in the centers of the tumor [ 41 ]. In the present study, a less blood-rich stroma was observed throughout the whole cross-section of the PC-3 PIP tumor ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zimmer 1995, 40 Wu 2019, 41 Ngen 2021, 42 Glover 2020, 43 Mathiasen 2019, 44 Schilham 2021, 45 Toth 2017, 46 Barajas 2019 47 Kelly 2020, 52 Rowe 2015, 53 Gorin 2016, 54 Rowe 2017, 55 Wilson 2020 56 PET Specific molecular targets; metabolism (glucose/glutamine) High sensitivity and potential for high specificity/complex infrastructure; costly agents (translational, clinical)…”
Section: Optical Techniquesmentioning
confidence: 99%
“…IRDye700DX is a hydrophilic phthalocyanine that readily forms conjugates with primary and secondary amino groups in targeting moieties, e.g., Cet [15][16][17][18]. An IRDye700DX-Cetconjugate has been given fast-track recognition by regulators in the USA and Japan [19].…”
Section: Introductionmentioning
confidence: 99%